Industrial services, product innovations, and firm profitability: A multiple-group latent growth curve analysis - Eggert, Andreas; Hogreve, Jens; Ulaga, Wolfgang; Muenkhoff, Eva (Industrial Marketing Management)

Exploring the Impact of Sales Technology on Salesperson Performance: A Task-Base d Approach - Eggert, Andreas; Serdaroglu, Murat (Journal of Marketing Theory and Practice)

Who follows the crowd—Groups or individuals? - Fahr, René; Irlenbusch, Bernd (Journal of Economic Behavior & Organization)

Job design and job satisfaction—empirical evidence for Germany? - Fahr, René (management revue)

When the early bird catches the worm: The impact of training in retail - Hinerasky, Christiane; Fahr, Rene

Key Account Management - Ivens, Björn; Eggert, Andreas (Handbuch Vertriebsmanagement)

HRM and the use of personnel services: an empirical analysis of German firms - Alewell, Dorothea; Hauff, Sven; Weiland, Katrin; Thommes, Kirsten (International journal of manpower)

HR outsourcing and service quality: theoretical framework and empirical evidence - Braun, Irene; Pull, Kerstin; Alewell, Dorothea; Störmer, Susi; Thommes, Kirsten (Personnel Review)

Workshop 16 Individuelle Förderung. Konzepte und Erfahrungen zur Berufsorientierung im Übergang - Beutner, Marc; Kremer, H.-Hugo; Zoyke, A. (bwp@ Spezial 5 - Hochschultage Berufliche Bildung 2011)

Fachtagung 19 (bwp@ Spezial 5 - Hochschultage Berufliche Bildung 2011)

Lernfeldansatz - 15 Jahre danach - Kremer, H.-Hugo; Tramm, T.; Tenberg, R. (bwp@ Berufs- und Wirtschaftspädagogik - online)

Room temperature spin relaxation length in spin light-emitting diodes - Soldat, Henning; Li, Mingyuan; Gerhardt, Nils C.; Hofmann, Martin R.; Ludwig, Arne; Ebbing, Astrid; Reuter, Dirk; Wieck, Andreas D.; Stromberg, Frank; Keune, Werner; Wende, Heiko (Applied Physics Letters)

Surface acoustic wave controlled carrier injection into self-assembled quantum dots and quantum posts - Krenner, Hubert J.; Völk, Stefan; Schülein, Florian J. R.; Knall, Florian; Wixforth, Achim; Reuter, Dirk; Wieck, Andreas D.; Kim, Hyochul; Truong, Tuan A.; Petroff, Pierre M. (physica status solidi (c))

Modellbasiertes Testen: Hype oder Realität? - Weißleder, Stephan; Güldali, Baris; Mlynarski, Michael; Törsel, Arne-Michael; Faragó, David; Prester, Florian; Winter, Mario (OBJEKTspektrum)
Manuelle Testerstellung verursacht hohe Kosten. Im Vergleich dazu bietet modellbasiertes Testen große Vorteile hinsichtlich Testautomatisierung, früher Fehlerfindung, Erhöhung der Testabdeckung, effizienten Testentwurfs und besserer Rückverfolgbarkeit. Die Einführung des modellbasierten Testens ist jedoch mit Investitionen verbunden, für die die Rendite häufig unklar erscheint. Dabei finden sich in der Literatur bereits etliche Erfahrungsberichte zur erfolgreichen Einführung von modellbasiertem Testen in unterschiedlichen Anwendungsdomänen. In diesem Artikel präsentieren wir einen Überblick über einige dieser Erfahrungsberichte.

TORC: test plan optimization by requirements clustering - Güldali, Baris; Funke, Holger; Sauer, Stefan; Engels, Gregor (Software Quality Journal)
Acceptance testing is a time-consuming task for complex software systems that have to fulfill a large number of requirements. To reduce this effort, we have developed a widely automated method for deriving test plans from requirements that are expressed in natural language. It consists of three stages: annotation, clustering, and test plan specification. The general idea is to exploit redundancies and implicit relationships in requirements specifications. Multi-viewpoint techniques based on RM-ODP (Reference Model for Open Distributed Processing) are employed for specifying the requirements. We then use linguistic analysis techniques, requirements clustering algorithms, and pattern-based requirements collection to reduce the total effort of testing against the requirements specification. In particular, we use linguistic analysis for extracting and annotating the actor, process and object of a requirements statement. During clustering, a similarity function is computed as a measure for the overlap of requirements. In the test plan specification stage, our approach provides capabilities for semi-automatically deriving test plans and acceptance criteria from the clustered informal textual requirements. Two patterns are applied to compute a suitable order of test activities. The generated test plans consist of a sequence of test steps and asserts that are executed or checked in the given order. We also present the supporting prototype tool TORC, which is available open source. For the evaluation of the approach, we have conducted a case study in the field of acceptance testing of a national electronic identification system. In summary, we report on lessons learned how linguistic analysis and clustering techniques can help testers in understanding the relations between requirements and for improving test planning.

Using rule overriding to improve reusability and understandability of Dynamic Meta Modeling specifications - Soltenborn, Christian; Engels, Gregor (Journal of Visual Languages & Computing)
Dynamic Meta Modeling (DMM) is a visual semantics specification technique targeted at languages based on a metamodel. A DMM specification consists of a runtime metamodel and operational rules which describe how instances of the runtime metamodel change over time. A known deficiency of the DMM approach is that it does not support the refinement of a DMM specification, e.g., in the case of defining the semantics for a refined and extended domain-specific language (DSL). Up to now, DMM specifications could only be reused by adding or removing DMM rules. In this paper, we enhance DMM such that DMM rules can override other DMM rules, similar to a method being overridden in a subclass, and we show how rule overriding can be realized with the graph transformation tool GROOVE. We argue that rule overriding does not only have positive impact on reusability, but also improves the intuitive understandability of DMM semantics specifications.

Individuelle Förderung - aber wie? Einblicke in das Innovationsprojekt InLab - Kremer, H.-Hugo; Frehe, Petra (Beilage Schule NRW)

Individuelle Förderung fördern. Das Wirtschaftspädagogische Graduiertenkolleg als Innovation in der Lehrkräfte- und Schulentwicklung - Sloane, Peter F. E.; Kremer, H.-Hugo (Beilage Schule NRW)

Kooperationsvorhaben berufliches Gymnasium und Bachelor Wirtschaftswissenschaften. Ein Paderborner Modellprojekt zur Berufs- und Studienorientierung - Kremer, H.-Hugo; Sandmann, D. (bwp@ Berufs- und Wirtschaftspädagogik - online)

Physiologische Beanspruchungsreaktionen bei der Anwendung von kopfgetragenen AR-Displays - Böckelmann, Irina; Schenk, Daniel; Rößler, Thoralf; Adler, Simon; Senft, Björn; Grubert, Jens; Mecke, Rüdiger; Huckauf, Anke; Urbina, Mario; Tümler, Johannes; Darius, Sabine

User Centered Design Process of OSAMi-D - Developing User Interfaces for a Remote Ergometer Training Application - Klompmaker, Florian; Senft, Björn; Nebe, Karsten; Busch, Clemens; Willemsen, Detlev (HEALTHINF 2011 - Proceedings of the International Conference on Health Informatics, Rome, Italy, 26-29 January, 2011)

Berufliche Bildung 2011, Fachtagung 19 - Kremer, H.-Hugo; Tramm, T. (bwp@ Berufs- und Wirtschaftspädagogik - online)

The Challenge of Renewable Energies & Decentralized Power Systems – State of the Art, Potentials & Perspectives - Krauter, Stefan (Proceedings of Decentralized Power Systems (DPS) 2011, Paderborn (Deutschland), 2. September 2011.)

Palladio-based performance blame analysis - Brüseke, Frank; Becker, Steffen; Engels, Gregor (Proceedings of the 16th International Workshop on Component-Oriented Programming (WCOP; satellite event of the CompArch 2011), Boulder Colorado, CO (USA))
Performance is an important quality attribute for business information systems. When a tester has spotted a performance error, the error is passed to the software developers to fix it. However, in component-based software development the tester has to do blame analysis first, i. e. the tester has to decide, which party is responsible to fix the error. If the error is a design or deployment issue, it can be assigned to the software architect or the system deployer. If the error is specific to a component, it needs to be assigned to the corresponding component developer. An accurate blame analysis is important, because wrong assignments of errors will cause a loss of time and money. Our approach aims at doing blame analysis for performance errors by comparing performance metrics obtained in performance testing and performance prediction. We use performance prediction values as expected values for individual components. For performance prediction we use the Palladio approach. By this means, our approach evaluates each component’s performance in a certain test case. If the component performs poorly, its component developer needs to fix the component or the architect replaces the component with a faster one. If no omponent performs poorly, we can deduce that there is a design or deployment issue and the architecture needs to be changed. In this paper, we present an exemplary blame analysis based on a web shop system. The example shows the feasibility of our approach.

Semi-automatische Ableitung externer Anpassungsmechanismen für selbst-adaptive Systeme - Nagel, Benjamin (Proceedings of the Software Engineering 2011 (SE 2011), Karlsruhe (Germany))

Search on Semi-Structured Data using Lucene Search Engine - Jovanovikj, Ivan

Kompetenzbegriff und Evaluation im beruflichen Bildungswesen - Beutner, Marc (Lehrerbildung phasenübergreifend denken. Facetten einer bundesweiten Debatte)

Introducing Narrative in Drama - Flotmann, Christina; Tönnies, Merle (Narrative in Drama: CDE Studies 18)

Multi-Objective Optimization of a Piezoelectric Sandwich Ultrasonic Transducer by Using Elitist Non-Dominated Sorting Genetic Algorithm - Hemsel, Tobias; Fu, Bo; Jing, Yi; Fu, Xuan (Key Engineering Materials)
The multi-objective optimal design of a piezoelectric sandwich ultrasonic transducer is studied. The maximum vibration amplitude and the minimum electrical input power are considered as optimization objectives. Design variables involve continuous variables (dimensions of the transducer) and discrete variables (material types). Based on analytical models, the optimal design is formulated as a constrained multi-objective optimization problem. The optimization problem is then solved by using the elitist non-dominated sorting genetic algorithm (NSGA-II) and Pareto-optimal designs are obtained. The optimized results are analyzed and the preferred design is proposed. The optimization procedure presented in this contribution can be applied in multi-objective optimization problems of other piezoelectric transducers.

Multi-DOF cylindrical piezoelectric actuator with radial polarization - Lucinskis, Raimundas; Mazeika, Dalius; Hemsel, Tobias; Bansevicius, Ramutis (AIP Conference Proceedings)
The paper presents the results of numerical and experimental investigation of cylindrical piezoelectric actuator used for achieving independent three degrees of freedom oscillations of the contact point. The design of actuator based on a hollow piezoelectric cylinder mounted on a metal rod. The piezoceramic cylinder has a radial polarization and special configuration of the electrodes that cover inner and outer surface of the cylinder. The main advantage of actuator's design is that solid metallic rod operates as a part of inner electrode of the cylinder and a stator of actuator. The geometry of piezoelectric actuator was adopted to reach resonance of oscillations for the first longitudinal mode and the third flexural mode at same frequency. The actuator is designed to move positioned object through contact point which is located on the top of the rod. The optimal topology of electrodes was found to achieve longitudinal and flexural oscillations of the actuator in two perpendicular planes. Three degrees of freedom of the positioning object can be achieved and control of the system can be implemented by applying different excitation schemes and regimes. The numerical simulation and experimental study of piezoelectric actuator was performed. Impedance of actuator was analyzed under different excitation regimes. The results of numerical modeling and experimental study were compared. Recommendations for the further development of this type of actuator are given.
Keywords: dielectric polarisation; piezoceramics; piezoelectric actuators

Dependability Analysis of the Degradation Behavior of Mechatronics Systems with Different Operating Strategies - Lurie, Oleg; Kromov, Ivan; Trächtler, Ansgar; Sondermann-Wölke, Christoph; Sextro, Walter (25. Tagung Technische Zuverlässigkeit (TTZ 2011) - Entwicklung und Betrieb zuverlässiger Produkte)

Improved Process for Hydrothermal Lead-Free Piezoelectric Powders and Performances of Sintered (K0.48Na0.52)NbO3 Ceramics - Maeda, Takafumi; Hemsel, Tobias; Morita, Takeshi (Japanese Journal of Applied Physics)
In this study, we report some improvements in a hydrothermal method for lead-free piezoelectric powders and the performance of the sintered (K$_{0.48}$Na$_{0.52}$)NbO$_{3}$ ceramics. To increase the obtained powder weight per source solution volume, the hydrothermal reaction conditions were modified. This improvement is important for mass production; however, it resulted in a larger particle size dispersion. Therefore, we examined to introduced the ball milling process that is useful for dense (K$_{0.48}$Na$_{0.52}$)NbO$_{3}$ ceramics. When a large amount of powder was obtained, it took a long time to eliminate the residual alkaline ions in the hydrothermal powders by a washing process. Therefore, a neutralization was conducted in the powder washing process. Using this powder, a solid solution of (K,Na)NbO$_{3}$ceramics was synthesized. The relative density was successfully increased. Concerning the electrical properties, the relative permittivity was improved, and the piezoelectric constant d$_{33}$ was also increased from 114 to 130 pC/N.

Component-based Hazard Analysis for Mechatronic Systems - Priesterjahn, Claudia; Sondermann-Wölke, Christoph; Tichy, Mathias; Hölscher, Christian (Proc. of the 2nd IEEE International Workshop MoBE-RTES at the 14th IEEE International Symposium on Object/Component/Service-oriented Real-time Distributed Computing (ISORC))
One cannot image today's life without mechatronic systems, which have to be developed in a joint effort by teams of mechanical engineers, electrical engineers, control engineers and software engineers. Often these systems are applied in safety critical environments like in cars or aircrafts. This requires systems that function correctly and do not cause hazardous situations. However, random errors due to wear or external influences cannot be completely excluded. Consequently, we have to perform a hazard analysis for the system. Further, the union of four disciplines in one system requires the development and analysis of the system as a whole. We present a component-based hazard analysis that considers the entire mechatronic system including hardware, i.e. mechanical and electrical components, and software components. Our approach considers the physical properties of different types of flow in mechatronic systems. We have identified reusable patterns for the failure behavior which can be generated automatically. This reduces the effort for the developer. As cycles, e.g. control cycles, are an internal part of every mechatronic system our approach is able to handle cycles. The presented approach has been applied to a real-life case study.

Zuverlässigkeitsorientierte Mehrzieloptimierung zur Aktorrekonfiguration eines X-by-wire-Fahrzeugs - Sondermann-Wölke, Christoph; Sextro, Walter; Reinold, Peter; Trächtler, Ansgar (25. Tagung Technische Zuverlässigkeit (TTZ 2011) - Entwicklung und Betrieb zuverlässiger Produkte)
Dieser Beitrag stellt ein Konzept vor, welches die Methode der Mehrzieloptimierung mit einer Online-Bewertung des aktuellen Systemzustands kombiniert. Dieses erlaubt Maßnahmen zur Zuverlässigkeitssteigerung abzuleiten. Das Konzept wird auf ein X-by-wire-Fahrzeug mit Einzelradaktorik angewandt. Dabei steht zunächst die Beeinflussung der Ziele der Mehrzieloptimierung zugunsten der Zuverlässigkeit des Systems im Vordergrund. In Simulationen wird gezeigt, dass über die Wahl und Gewichtung der Zielfunktionen die Quer- und Längskräfte an den Rädern vorteilhaft verteilt werden können. In this contribution a concept is illustrated, which combines the multi-objective optimization technique with an online assessment of the current system state. This allows deriving measures to increase the reliability of the system. The concept is applied to an X-by-wire vehicle with single-wheel actuators. The emphasis is here mostly on the influence of the objectives of the multiobjective optimization for the benefit of the reliability of the system. It is demonstrated in simulations, that the lateral and longitudinal forces at the wheels can be distributed advantageously by the selection of the suitable objective functions and the appropriate weights.

Friction in wheel--rail contact: A model comprising interfacial fluids, surface roughness and temperature - Tomberger, Christoph; Dietmaier, Peter; Sextro, Walter; Six, Klaus (Wear)
A profound description of friction in wheel--rail contact plays an essential role for optimization of traction control strategies, as input quantity for railway simulations in general and for the estimation of wear and rolling contact fatigue. A multitude of wheel--rail contact models exists, however, traction--creepage curves obtained from measurements show quantitative and qualitative deviations. There are several phenomena which influence the traction--creepage characteristics: Mechanisms resulting from surface roughness, frictional heating or the presence of interfacial fluids can have a dominating influence on friction. In this paper, a new wheel--rail contact model, accounting for these influential parameters, will be presented. The presented model accounts for the interaction of an interfacial fluid model for combined boundary and mixed lubrication of rough surfaces with a wheel--rail contact model that additionally accounts for frictional heating. A quantitative comparison with measurements found in the literature is not conducted, since the exact conditions of the measurements are mostly unknown and parameters can easily be adjusted to fit the measurements. Emphasis is placed on the qualitative behavior of the model with respect to the measurements and good agreement is found. The dependence of the maximum traction coefficient on rolling velocity, surface roughness and normal load is studied under dry and water lubricated conditions.
Keywords: Wheel--rail contact; Rolling contact; Friction; Interfacial fluid; Lubrication; Surface roughness; Contact temperature

High temperature tolerant transducer for Ultrasonic Assisted Hydrothermal Method - Isobe, Gaku; Bornmann, Peter; Hemsel, Tobias; Morita, Takeshi (Proceedings of Symposium on Ultrasonic Electronics)

Narrative in Drama

Phonon-assisted decoherence and tunneling in quantum dot molecules - Grodecka-Grad, Anna; Förstner, Jens (physica status solidi (c))
We study the influence of the phonon environment on the electron dynamics in a doped quantum dot molecule. A non-perturbative quantumkinetic theory based on correlation expansion is used in order to describe both diagonal and off-diagonal electron-phonon couplings representing real and virtual processes with relevant acoustic phonons. We show that the relaxation is dominated by phononassisted electron tunneling between constituent quantum dots and occurs on a picosecond time scale. The dependence of the time evolution of the quantum dot occupation probabilities on the energy mismatch between the quantum dots is studied in detail.
Keywords: tet_topic_qd

Relaxation of a strained 3C-SiC(111) thin film on silicon by He+ and O+ ion beam defect engineering - Häberlen, M.; Murphy, B.; Stritzker, B.; Lindner, Jörg (Nuclear Instruments and Methods in Physics Research Section B: Beam Interactions with Materials and Atoms)
In this paper we report on the successful reduction of tensile strain in a thin strained ion-beam synthesized 3C-SiC(1 1 1) layer on silicon. The creation of a near-interface defect structure consisting of nanometric voids and stacking fault type defects by He ion implantation and subsequent annealing yields significant relaxation in the top SiC film. The microstructure of the defect layer is studied by transmission electron microscopy, and the strain state of the 3C-SiC layer was studied by high-resolution X-ray diffraction in a parallel beam configuration. Typical process conditions for the growth of GaN films on the SiC layer were emulated by high temperature treatments in a rapid thermal annealer or a quartz tube furnace. It is found that prolonged annealing at high temperatures leads to ripening of the voids and to a weaker reduction of the tensile strain. It is shown that this problem can be overcome by the co-implantation of oxygen ions to form highly thermally stable void/extended defect structures.

Decoupling of a strained 3C-SiC(111) thin film on silicon by He+ and O+ ion implantation - Häberlen, Maik; Murphy, Brian; Stritzker, Bernd; Lindner, Jörg (physica status solidi (c))
This paper reports the successful reduction of tensile strain in a thin ion-beam-synthesized 3C-SiC(111) layer on silicon. Significant relaxation is achieved by creating a near-interface defect structure containing nanometric voids and dislocation loops by the implantation of He ions and subsequent thermal annealing. The structural features of this defect microstructure are investigated by transmission electron microscopy. High-resolution X-ray diffraction in a parallel beam configuration is used to quantify the strain state of the top SiC layer. Further annealing experiments were carried out in order to emulate typical process conditions for the growth of wide-bandgap semiconductors like, for example GaN. It is found that prolonged annealing at elevated temperatures leads to coarsening of the voids and to a much less efficient strain reduction. We show that this issue can be resolved by the co-implantation of oxygen to form highly thermally stable cavity/extended defect structures. The technique presented here may be useful for a variety of other thermally mismatched bulk/thin film couples as well.

Photoluminescence properties of Sm2+-doped BaBr2 under hydrostatic pressure - Wiegand, Marie Christin; Sievers, Werner; Lindner, Jörg; Tröster, Th.; Schweizer, S. (Journal of Luminescence)
Photoluminescence spectra of Sm^(2+)-doped BaBr^2 have been measured under hydrostatic pressures up to 17 GPa at room temperature. In the low pressure range a red-shift of the broad 5d–4f transition of -145 cm^(-1)/GPa is observed. From 5 to 8 GPa a phase mixtureof the initial orthorhombic phase and the high-pressure monoclinic phase gives rise to two 5d–4f bands, which are strongly overlapping. Above 8 GPa the crystalis completely transformed to its high-pressure phase where two different Sm2^(2+) sites exist, but only one broad 5d–4f transition is detected. It exhibits are d-shift of -36 cm^(-1)/GPa. In addition,the line shifts of the (_^5)D_0→(_^7)F_J (J=0,1,2) transitions are investigated. Linear shifts of -19cm^(-1)/GPa for J=0,2 and of -13cm^(-1)/GPa for J01 are observed in the pressure range from 0 to 5 GPa.

Combinedab initioand classical potential simulation study on silicon carbide precipitation in silicon - Zirkelbach, F.; Stritzker, B.; Nordlund, K.; Lindner, Jörg; Schmidt, W. G.; Rauls, E. (Physical Review B)
Atomistic simulations on the silicon carbide precipitation in bulk silicon employing both, classical potential and first-principlesmethods are presented. The calculations aim at a comprehensive,microscopic understanding of the precipitation mechanism in the context of controversial discussions in the literature. For the quantum-mechanical treatment, basic processes assumed in the precipitation process are calculated in feasible systems of small size. The migration mechanism of a carbon 100 interstitial and silicon 11 0 self-interstitial in otherwise defect-free silicon are investigated using density functional theory calculations. The influence of a nearby vacancy, another carbon interstitial and a substitutional defect as well as a silicon self-interstitial has been investigated systematically. Interactions of various combinations of defects have been characterized including a couple of selected migration pathways within these configurations. Most of the investigated pairs of defects tend to agglomerate allowing for a reduction in strain. The formation of structures involving strong carbon–carbon bonds turns out to be very unlikely. In contrast, substitutional carbon occurs in all probability. A long range capture radius has been observed for pairs of interstitial carbon as well as interstitial carbon and vacancies. A rather small capture radius is predicted for substitutional carbon and silicon self-interstitials. Initial assumptions regarding the precipitation mechanism of silicon carbide in bulk silicon are established and conformability to experimental findings is discussed. Furthermore, results of the accurate first-principles calculations on defects and carbon diffusion in silicon are compared to results of classical potential simulations revealing significant limitations of the latter method. An approach to work around this problem is proposed. Finally, results of the classical potential molecular dynamics simulations of large systems are examined, which reinforce previous assumptions and give further insight into basic processes involved in the silicon carbide transition.

Paying for Performance in Hospitals - Hehenkamp, Burkhard; Kaarboe, Oddvar (Economic Analysis and Policy)

Method for transmission of information about polarization state of photons to stationary system - Förstner, Jens; Mantei, D.; de Vasconcellos, S. Michaelis; Zrenner, Artur
The method involves exciting a quantum system with photons in a polarization state. Two states of the quantum system are excited with linear horizontal and vertical polarizations that are orthogonal to each other, where the states exhibit an energetic gap smaller than energetic bandwidth of photons. The states are assigned based on the polarizations, where the quantum system is arranged in a superposition state. The quantum system is formed by a quantum bit that is formed as a two-level system.
Keywords: tet_topic_qd

Imaging of the Ferroelectric Domain Structures by Confocal Raman Spectroscopy - Berth, Gerhard; Hahn, Wjatscheslaw; Wiedemeier, Volker; Zrenner, Artur; Sanna, Simone; Schmidt, Wolf Gero (Ferroelectrics)
Confocal Raman spectroscopy was performed as an archetype imaging method to study the ferroelectric domain structure of periodically poled lithium niobate. More precisely, the linkage out of spatial resolution and spectral information proved itself as very useful. Here a specific modulation of the Raman lines by the local variation of polarity and a non-symmetric measuring-signal across the domain structure were found, which allows for imaging of domain boundaries as well as oppositely orientated domains. The high potential of this method is demonstrated by the visualization of the ferroelectric domain structures based on various phonon modes.
Keywords: Raman spectroscopy; ferroelectric domains; LiNbO3; confocal imaging

Electrically driven intentionally positioned single quantum dot - Mehta, Minisha; Reuter, Dirk; Wieck, Andreas D.; Michaelis de Vasconcellos, Steffen; Zrenner, Artur; Meier, Cedrik (physica status solidi (c))
Using a combined all-ultra-high-vacuum process employing lateral patterning with focused ion beams and molecular beam epitaxy, site-selective growth of single (In,Ga)As quantum dots is achieved. We have embedded such a layer of intentionally positioned quantum dots in the intrinsic region of a p-i-n junction so that the quantum dots can be driven electrically. In this contribution, we will present our results on the morphological properties of the ion-beam modified surface on which the quantum dot nucleation occurs together with a characterization of the electrical and optoelectronic properties. We will demonstrate that a single, individual quantum dot can directly be electrically addressed.
Keywords: molecular beam epitaxy; quantum dot; site control; electroluminescence

Lift-off of mesoporous layers by electrochemical etching on Si (100) substrates with miscut of 6° off towards (111) - Garralaga Rojas, E.; Terheiden, B.; Plagwitz, H.; Hensen, J.; Wiedemeier, V.; Berth, Gerhard; Zrenner, Artur; Brendel, R. (Thin Solid Films)
Uniform mesoporous Si double layers are formed on 4 inch p-type < 100> wafers with an off orientation of 6º towards < 111> by means of electrochemical etching in ethanoic-based HF electrolytes. These substrates are of interest for the epitaxial growth of III–V compound semiconductor stacks on their top for the production of multi-junction solar cells and very thin electronic devices. We demonstrate transfer of porous layers after an annealing process in hydrogen atmosphere. Electron Back-Scatter Diffraction analysis confirms that the substrate orientation is conserved during the etching and annealing steps. Confocal μ-Raman spectroscopy analysis shows a decrease in the Raman signal intensity after etching and a subsequent increase after annealing while no shift is observed. By means of Atomic Force Microscopy, analysis the surface appearance after the etching and annealing steps can be visualized. The mean surface roughness varies during the process from 0.55 nm for the unprocessed wafers to 0.27 nm after etching and 0.78 nm after annealing. The decrease of average roughness after etching is caused by an electropolishing step prior to porous formation. Despite of slight increase of mean surface roughness after annealing the samples are still appropriate for high quality epitaxial growth and subsequent lift-off.
Keywords: Porous Si; Layer transfer; Thin-film; Photovoltaics

Integrierte Informationslogistik in der hybriden Wertschöpfung - Becker, Jörg; Beverungen, Daniel; Knackstedt, Ralf; Matzner, Martin; Müller, Oliver; Pöppelbuß, Jens (Mit Dienstleistungen die Zukunft gestalten: Impulse aus Forschung und Praxis. Beiträge der 8. Dienstleistungstagung des BMBF)

Engineering, Sales, and Delivery of Modular Value Bundles --- A Framework for Configurative Modeling - Becker, Jörg; Beverungen, Daniel; Knackstedt, Ralf; Stein, Armin (Implementing International Services: A tailorable method for market assessment, modularization, and process transfer)

Die Besteuerung multinationaler Unternehmen in der Europäischen Union - Bäumer, Michaela

Der Einfluss von Mindestbesteuerungskonzepten auf unternehmerische Investitionsentscheidungen unter Berücksichtigung grenzüberschreitender Gruppenbesteuerungssysteme - Dahle, Claudia

Die Einkommensbesteuerung von international tätigen Künstlern, Sportlern, Artisten und unterhaltend Darbietenden - Führt die Neuregelung zu einer gleichmäßigen Besteuerung? - Dahle, Claudia; Sureth-Sloane, Caren; Stamm, Katharina (Steuern und Bilanzen)

Economic Analysis of Advance Tax Rulings - Diller, Markus; Vollert, Pia

Die Besteuerung von Veräußerungsgewinnen und Investitionsverhalten bei Risiko - Halberstadt, Alexander

ProDok Helps to Transform Doctoral Training at Business Schools in German-Speaking Countries - Jahnke, Hermann; Sureth-Sloane, Caren (POMS Chronicle)

Für Wissenschaft, Praxis und Gesellschaft - Sureth-Sloane, Caren; Wagenhofer, Alfred (Frankfurter Allgemeine Zeitung)

Zur Neuregulierung des Bankensektors nach der Finanzkrise: Bewertung der Reformvorhaben der EU aus ordnungspolitischer Sicht - Haucap, Justus; Heimeshoff, Ulrich; Uhde, André (Die aktuelle Finanzkrise: Bestandsaufnahme und Lehren für die Zukunft, Schriften zur Ordnungsfragen der Wirtschaft)
Im Zuge der in den USA durch die exzessive Vergabe von Subprime-Krediten und deren Verbriefung ausgelöste Finanzkrise und der daraus folgenden weltweiten Wirtschaftskrise hat sich gezeigt, dass das bisherige System der Regulierung bzw. Überwachung von Finanzinstitutionen nicht ausreichend ist. Sowohl in den USA als auch in der Europäischen Union wird deshalb intensiv über ein neues System zur Regulierung von Finanzinstituten nachgedacht. Es ist zwar offen-sichtlich, dass eine wesentliche Ursache der Finanzkrise in den USA die Ermunterung der Finanzinstitute durch den Staat zur Vergabe von Immobilienkrediten an nicht ausreichend solvente Konsumenten war. Die vorhandenen Regulierungsinstrumente konnten die Krise jedoch nicht verhindern bzw. ausreichen abmildern. Das vorliegende Papier setzt sich zum Ziel, die Vorschläge zur Reform der Bankenregulierung zu evaluieren und insbesondere auf ihre potenziellen Wirkungen im Hinblick auf den Wettbewerb im Bankensektor zu überprüfen. Im Zuge der Diskussion über mögliche Lösungen existieren verschiedenste Vorschläge, die von Änderungen in Rechnungslegungsvorschriften über die Neuordnung der nationalen bzw. internationalen Finanzaufsicht bis hin zu einer stärkeren Berücksichtigung systemischer Risiken gehen. Die Auswirkungen der Finanzkrise haben gezeigt, dass die Abkehr von herkömmlichen Rechnungslegungssystemen hin zu Regeln der internationalen Rechnungslegung unter dem Schlagwort „Fair Value Accounting“ durchaus Gefahren in sich bergen kann. Die Debatte dreht sich insbesondere um die Frage, ob die neuen Rechnungslegungsvorschriften maßgeblich dazu beitragen, das regulatorische Eigenkapital einer Bank in Boomphasen zu erhöhen und in konjunkturellen Schwächephasen dagegen zu senken. In der Literatur ist in Hinblick auf diese Frage bislang keine einhellige Auffassung zu identifizieren. Pellens et al. (2009) gelangen zu dem Ergebnis, dass bankenaufsichtsrechtliche Normen an das IFRS-Zahlenwerk gebunden sind und dies für regulatorische Entscheidungen als besonders kritisch zu sehen ist. Durch das Konzept des Fair-Value-Accounting wurde das regulatorische Eigenkapital im Zeitraum von 2003 bis 2007 systematisch erhöht, woraus ein gestiegener Kreditvergabespielraum resultierte. Demgegenüber kommen Laux und Leuz (2009) im Rahmen einer empirischen Studie anhand von Mikrodaten aus den USA zu dem Ergebnis, dass Fair-Value-Accounting nur zum geringen Teil zu den Problemen der US Banken beigetragen hat und es im Rahmen ihrer Studie keine Evidenz für wesentliche Effekte dieses Rechnungslegungsverfahrens auf die massiven Abschreibungen der US Banken gibt. Beide Studien betonen aber auch, dass weitere empirische Forschung notwendig ist, bevor diese Frage abschließend geklärt werden kann. Die Frage des adäquaten Rechnungslegungssystems zeigt, wie vielfältig die Ursachen der gegenwärtigen Finanzkrise sind und wie schwer tatsächliche kausale Effekte zu identifizieren sind. Im folgenden Abschnitt werden zunächst die ordnungspolitischen Rahmenbedingungen einer angemessenen Bankenregulierung dargestellt. Der dritte Abschnitt umfasst einen kurzen Überblick über den Verlauf der Finanzkrise. In Abschnitt 4 diskutieren wir die wesentlichen Vorschläge zur Optimierung der Regulierung von Finanzinstituten. Abschnitt 5 evaluiert diese Vorschläge auch aus einer wettbewerbsökonomischen Perspektive. Diese Perspektive ist aus unserer Sicht vor allen Dingen notwendig, weil eine großer Teil der Reformdebatte aus Sicht der Finanzmarktstabilität geführt wird und infolgedessen Wettbewerbseffekte vernachlässigt werden. Das Fazit in Abschnitt 6 fasst unsere Ergebnisse zusammen und gibt einen Ausblick auf weiteren Forschungsbedarf aus Sicht der Wettbewerbsökonomie.

Unternehmensbewertung in Deutschland: Verfahren, Finanzplanung und Kapitalkostenermittlung - Homburg, Carsten; Lorenz, Michael; Sievers, Sönke (Controlling & Management)

Adverse selection, investor experience and security choice in venture capital finance: evidence from Germany - Hartmann-Wendels, Thomas; Keienburg, Georg; Sievers, Sönke (European Financial Management (VHB-JOURQUAL 3 Ranking B))
This article analyses 336 German venture capital transactions from 1990 to 2005 and seeks to determine why selected financial securities differ across deals. We find that a broad array of financial instruments is used, covering straight equity, mezzanine and debt‐like securities. Based on the chosen financial securities’ upside potential and downside protection characteristics, we provide an explanation for the differing use of these securities. Our results show that investors’ deal experience, adverse selection risks and economic prospects in the public equity market influence the selection of financial securities.
Keywords: venture capital; capital structure; contract theory; deal experience

Zusatzbeiträge erhöhen die Preistransparenz: mehr Versicherte wechseln die Krankenkasse - Schmitz, Hendrik; Eibich, P.; Ziebarth, N.R. (Wochenbericht)

Kosteneffizienz Deutscher Krankenhäuser im Bundeslandvergleich - Schmitz, Hendrik; Augurzky, B.

Objective work-nonwork conflict: From incompatible demands to decreased work role performance. - Haun, S; Steinmetz, Holger; Dormann, C (Journal of Vocational Behavior.)

A Need-Based Approach to Organizational Commitment and Job Involvement: Cross-Cultural Evidence from Germany and South Korea. - Steinmetz, Holger; Park, Y K; Kabst, Rüdiger (Journal of Managerial Psychology.)

A Typology of International New Ventures: Empirical Evidence from High Technology Industries. - Baum, M; Schwens, C; Kabst, Rüdiger (Journal of Small Business Management (JSBM).)

An Exploratory Cross-National Study of Information Sharing and Human Resource Information Systems. - Chae, B; Prince, J B; Katz, J; Kabst, Rüdiger (Journal of Global Information Management.)

Arbeitgebermarkenaufbau durch informelle Hochschul-Personalmarketingmaßnahmen: Eine empirische Analyse im deutschen Mittelstand. - Baum, M; Kabst, Rüdiger (Zeitschrift für Betriebswirtschaft (ZfB).)

Conceptual and Methodological Issues in Comparative HRM Research: The Cranet Project. - Steinmetz, Holger; Schwens, C; Wehner, M C; Kabst, Rüdiger (Human Resource Management Review (HRMR).)

Entry Learning, Age at Internationalization, and Foreign Venture Performance of Young Technology Firms. - Schwens, C; Kabst, Rüdiger (Schmalenbach Business Review (sbr).)

High involvement information sharing practices: An international perspective. - Prince, J B; Katz, J; Kabst, Rüdiger (International Journal of Human Resource Management.)

Human Resource Management and Early Internationalization: Is there a Leap-Frogging in International Staffing? - Isidor, R; Schwens, C; Kabst, Rüdiger (International Journal of Human Resource Management (IJHRM).)

International Entrepreneurship: A Meta-Analysis. - Schwens, C; Isidor, R; Bierwerth, M; Kabst, Rüdiger (Best Paper Proceedings of the 2011 Academy of Management.)

Internationalization of young technology firms: A complementary perspective on antecedents of foreign market familiarity. - Schwens, C; Kabst, Rüdiger (International Business Review (IBR).)

The Moderating Impact of Informal Institutional Distance and Formal Institutional Risk on SME Entry Mode Choice. - Schwens, C; Eiche, J; Kabst, Rüdiger (Journal of Management Studies (JMS).)

Three Approaches to Estimate Latent Interaction Effects: Intention and Perceived Behavioral Control in the Theory of Planned Behavior. - Steinmetz, Holger; Davidov, E; Schmidt, P (Methodological Innovation)

Intelligent Decision Support for Centralized Coordination during Emergency Response - Wex, Felix; Schryen, Guido; Neumann, Dirk (Proceedings of the 8th International Conference on Information Systems for Crisis Response and Management (ISCRAM 2011))

A formal approach towards measuring trust in distributed systems - Schryen, Guido; Volkamer, Melanie; Ries, Sebastian (Proceedings of the 26th Annual ACM Symposium on Applied Computing)

Is open source security a myth? What do vulnerability and patch data say? - Schryen, Guido (Communications of the ACM (CACM))

Seeking the VALUE in IS Business Value Research - An Agenda for investigating Synergies Between Socio-organizational Change, IS Capabilities Change, and IS Innovation - Schryen, Guido (IS Capabilities Change, and IS Innovation, Proceedings of the 19th European Conference on Information Systems (ECIS 2011), Helsinki)

Self-Stabilizing DeBruijn Networks - Richa, Andrea W.; Scheideler, Christian (Proceedings of the 13th International Symposium on Stabilization, Safety, and Security of Distributed Systems (SSS))
This paper presents a dynamic overlay network based on the De Bruijn graph which we call Linearized De Bruijn (LDB) network. The LDB network has the advantage that it has a guaranteed constant node degree and that the routing between any two nodes takes at most O(log n) hops with high probability. Also, we show that there is a simple local-control algorithm that can recover the LDB network from any network topology that is weakly connected.

Editorial bwp@ 20 - Tramm, T.; Kremer, H.-Hugo; Tenberg, R. (bwp@ Ausgabe 20, Lernfeldansatz 15 Jahre danach)

Bildungsmaßnahmen zur Berufsorientierung im Justizvollzug - Konzept und Erfahrungen - Beutner, Marc; Kremer, H.-Hugo; Wirth, W. (bwp@ Spezial 5 - Hochschultage Berufliche Bildung 2011, Workshop 16)

Editorial zu Workshop 16: Individuelle Förderung - Konzepte und Erfahrungen zur Berufsorientierung im Übergang - Beutner, Marc; Kremer, H.-Hugo; Zoyke, A. (WS 16 Individuelle Förderung. Konzepte und Erfahrungen zur Berufsorientierung im Übergang. bwp@ Spezial 5 - Hochschultage Berufliche Bildung 2011)

Praxisphasen und Professionalisierung in der Lehrerbildung - Überlegungen zur Gestaltung des Praxissemesters - Kremer, H.-Hugo (Wirtschaftspädagogik zwischen Erkenntnis und Erfahrung - strukturelle Einsichten zur Gestaltung von Prozessen)

Innovationen in berufsbildenden Kontexten - eine explorative Studie an berufsbildenden Schulen - Ertl, H.; Kremer, H.-Hugo (Wirtschaft und Erziehung)

Selected papers on Integrated Formal Methods (iFM09) - Leuschel, Michael; Wehrheim, Heike (Science of Computer Programming)

Berufsorientierung als Herausforderung für berufsbildende Schulen! - Kremer, H.-Hugo (bwp@ Sepzial 5 - Hochschultage Berufliche Bildung 2011, Workshop 02)

Zwischenbilanz des Lernfeldkonzepts - erfolgreiche Neuorientierung oder Irrweg - Tramm, T.; Kremer, H.-Hugo (Übergänge in der Berufsbildung nachhaltig gestalten: Potentiale erkennen - Chancen nutzen)

Editorial Fachtagung Wirtschaft und Verwaltung: Zwischenbilanz des Lernfeldkonzepts - erfolgreiche Neuorientierung oder Irrweg - Kremer, H.-Hugo; Tramm, T. (bwp@ Sepzial 5 - Hochschultage Berufliche Bildung 2011, Fachtagung 19)

Kooperationsvorhaben ‚berufliches Gymnasium‘ und Bachelor Wirtschaftswissenschaften. Ein Paderborner Modellprojekt zur Berufs- und Studienorientierung - Kremer, H.-Hugo; Sandmann, D. (bwp@ Spezial 5 - Hochschultage Berufliche Bildung 2011, Workshop 29)

bwp@ Berufs- und Wirtschaftspädagogik - online 2011-2011: Verortung, Selbstverständnis und Entwicklung - Büchter, K.; Gramlinger, F.; Kremer, H.-Hugo; Tenberg , R.; Tramm, T. (bwp@ Berufs- und Wirtschaftspädagogik - online, Jubiläumsausgabe)

Robust Distributed Computation in Dynamic Networks - Brandes, Philipp

Reputation-based Reliability Prediction of Service Compositions - Besova, Galina; Wehrheim, Heike; Wagner, Annika (Electronic Notes in Theoretical Computer Science)
Today, the concept of service oriented architectures provides a way of building integrated solutions out of existing services. To this end, services from different providers are composed using advanced orchestration and choreography techniques. However, while this principle allows for greater flexibility at a smaller cost, the use of third party services also includes a risk: Deployed services might not work as claimed by their providers. In this paper, we propose a technique for analyzing the expected reliability of service compositions based on ratings given by (previous) service users. Every service thereby comes with a reputation, and the analysis computes an overall reliability of a service composition from the reputations of its constituent services. The proposed model-driven approach proceeds by translating statechart models of service compositions into input for a probabilistic model checker (PRISM) using state-of-the-art model transformations techniques. The approach has been implemented as an Eclipse plug-in and is fully compliant with UML.

Reengineering of Design Deficiencies in Component-Based Software Architectures - Platenius, Marie Christin

Prozedurale Ansätze zur Lösung mehrdimensionaler Verhandlungsprobleme - Stroh-Maraun, Nadja

Precise Mappings between Business Process Models in Versioning Scenarios - Gerth, Christian; Luckey, Markus; Küster, Jochen; Engels, Gregor (Proceedings of the IEEE 8th International Conference on Service Computingt (SCC))
In the development process of service-oriented systems, business process models are used at different levels. Typically, high-level business process models that describe business requirements and needs are stepwise refined to the IT level by different business modelers and software architects. As a result, different process model versions must be compared and merged by means of model version control. An important prerequisite for process model version control is an elaborated matching approach that results in precise mappings between different process model versions. The challenge of such an approach is to deal with syntactically different process models that are semantically equivalent. For that purpose, matching techniques must consider the semantics of process modeling languages.In this paper, we present a matching approach for process models in a versioning scenario. Based on a term formalization of process models, we enable an efficient and effective way to match syntactically different but semantically equivalent process models resulting in precise mappings.

Performance Prototyping with ProtoCom in a Virtualised Environment: A Case Study - Lehrig, Sebastian; Zolynski, Thomas (Proceedings of the Palladio Days 2011)
Performance prototyping is an often used technique to assess the performance of software architectures early in the development process without relying on models of the system under study. ProtoCom is a prototype generator for the PCM realised as model-2-text transformation for which no experience report in a larger, virtualised setting exists. In this paper, we report on four case studies performed with an improved version of ProtoCom and report on the results gained with respect to analysis accuracy and usability. Our results demonstrate that the new version is much easier to use than previous versions and that results gained in our virtualised execution environment help in early assessments of performance under realistic conditions.

PeerfactSim.KOM: A PSP System Simulator - Experiences and Lessons Learned - Graffi, Kalman (Proceedings of the IEEE International Conference on Peer-to-Peer Computing (IEEE PsP))
Research on peer-to-peer (p2p) and distributed systems needs evaluation tools to predict and observe the behavior of protocols and mechanisms in large scale networks. PeerfactSim.KOM is a simulator for large scale distributed/p2p systems aiming at the evaluation of interdependencies in multi-layered p2p systems. The simulator is written in Java, is event-based and mainly used in p2p research projects. The main development of PeerfactSim.KOM started in 2005 and is driven since 2006 by the project “QuaP2P”,which aims at the systematic improvement and benchmarking of p2p systems. Further users of the simulator are working in the project “On-the-ﬂy Computing” aiming at researching p2p-based service oriented architectures. Both projects state severe requirements on the evaluation of multi-layered and large-scale distributed systems. We describe the architecture of PeerfactSim.KOM supporting these requirements in Section II, present the workﬂow, selected experiences and lessons learned in Section III and conclude the overview in Section IV.

Modellgetriebene Skalierbarkeitsanalyse von selbst-adaptiven Komponentenbasierten Softwaresystemen in der Cloud - Meyer, Joachim

Local Approximation Algorithms for the Uncapacitated Metric Facility Location Problem in Power-Aware Sensor Networks - Abshoff, Sebastan; Cord-Landwehr, Andreas; Degener, Bastian; Kempkes, Barbara; Pietrzyk, Peter (Proceedings of the 7th International Symposium on Algorithms for Sensor Systems, Wireless Ad Hoc Networks and Autonomous Mobile Entities (ALGOSENSORS))
We present two distributed, constant factor approximation algorithms for the metric facility location problem. Both algorithms have been designed with a strong emphasis on applicability in the area of wireless sensor networks: in order to execute them, each sensor node only requires limited local knowledge and simple computations. Also, the algorithms can cope with measurement errors and take into account that communication costs between sensor nodes do not necessarily increase linearly with the distance, but can be represented by a polynomial. Since it cannot always be expected that sensor nodes execute algorithms in a synchronized way, our algorithms are executed in an asynchronous model (but they are still able to break symmetry that might occur when two neighboring nodes act at exactly the same time). Furthermore, they can deal with dynamic scenarios: if a node moves, the solution is updated and the update affects only nodes in the local neighborhood. Finally, the algorithms are robust in the sense that incorrect behavior of some nodes during some round will, in the end, still result in a good approximation. The first algorithm runs in expected O(log_{1+ε} n) communication rounds and yields a \my^4(1+4\my^2(1+ε)^{1/p})^p approximation, while the second has a running time of expected O(log^2_{1+ε} n) communication rounds and an approximation factor of \my^4(1 + 2(1 + ε)^{1/p})^p. Here, ε > 0 is an arbitrarily small constant, p the exponent of the polynomial representing the communication costs, and \my the relative measurement error.

Function Specification Inference Using Craig Interpolation - Schremmer, Alexander